The association of cortisol levels with leukocyte distribution is disrupted in the metabolic syndrome - Mauss, Daniel; Herr, Raphael; Jarczok, Marc N.; Motoc, Irina; Fischer, Joachim E.; Bosch, Jos A. (Obesity research & clinical practice, 2021)
Background - Leukocyte glucocorticoid sensitivity (GCS) pertains to the responsivity of leukocytes to the regulating actions of glucocorticoids, such as cortisol. Impaired endocrine regulation may link the metabolic syndrome (MetS) to the development of cardiovascular disease. We tested if the physiological association between endogenous cortisol levels and peripheral leukocyte composition becomes disrupted in individuals with MetS. - Methods - MetS was assessed among 689 German industrial employees. The covariance between cortisol levels and hematologic parameters (i.e., proportions of neutrophils and lymphocytes) and their ratio was explored, which has been proposed as a proxy for GCS in vivo. Cortisol level before blood collection was assessed by repeated saliva collection, and the area under the curve was calculated. Linear regression models were adjusted for potential confounders including age, gender, BMI, income, and lifestyle factors. - Results - Cortisol levels did not differ between subgroups. Participants without MetS (n = 552) showed the expected association of cortisol with hematologic parameters (β = 0.207 to 0.216; p values < 0.001). No association (β = 0.078 to 0.083; p values > 0.10) was found among those with MetS (n = 137), consistent with a reduced GCS. Analyses of separate MetS components showed that reduced GCS was associated specifically with decreased high-density lipoprotein and elevated fasting plasma glucose. - Conclusions - Utilizing a novel statistical approach to infer GCS, this study provided first epidemiological evidence of aberrant physiological regulation of leukocyte distribution by endogenous cortisol levels among individuals with MetS. These findings underline the idea that MetS may involve disruption of endocrine-immune regulation.
Gesehen am 16.04.2021